Using Role Play Activities to Teach The Present Perfect Tense - Samia CHOUIEB (Revue des Sciences Humaines, 2018)
Teaching languages has continuously been centered on teaching their grammars which in turn focuses on teaching tenses. This research aims at investigating the effectiveness of using Role Play to teach the Present Perfect. It also seeks to analyze the attitudes of grammar teachers and their implementation of Role Play to teach the Present Perfect, at the Department of Letters and English, University ‘Des Frères Mentouri’, Constantine.  We hypothesize that, first, if teachers of grammar are made aware of the importance of using Role Play to teach the Present Perfect, they will have positive attitudes towards its implementation in their own classes. Second, if teachers use Role Play in their teaching of the Present Perfect, it will help the students understand and use this tense adequately.  To test our hypotheses, a Teachers’ Questionnaire and a Students’ Test are used. The analysis of the questionnaire shows that teachers of grammar hold positive attitudes towards using Role Play to teach the Present Perfect which totally confirms our first hypothesis. The sample (70 learners) is taken from second year students of English, at the Department of Letters and English, University ‘Des Frères Mentouri’, Constantine, during the academic year 2014/2015. The results obtained from the test partially confirm the second hypothesis, in other words, Role Play has succeeded to some extent to better the students’ understanding and use of the Present Perfect.